Studi Netnografi Pemanfaatan Media Sosial Instagram Sebagai Media Promosi Konten Wisata Kabupaten Gresik - Anita Rahmania; Aries Kurniawan (Research and Strategic Studies Center (Pusat Riset dan Kajian Strategis) Fakultas Syariah IAI Nasional Laa Roiba, 2024)
Many beautiful natural attractions, as well as other tours, await tourists in Gresik. Thanks to Instagram, a popular social media platform, visitors from all over the world are now familiar with Gresik's tourism attractions. This research aims to understand the dynamics of Instagram video content uploads in the context of using Instagram as a promotional tool for tourism sites in the Gresik area. Qualitative research methodology using netnography is used in this article. The results show that Instagram promotional videos for tourism attractions have become a popular way to promote tourism attractions in Gresik. The effectiveness of these videos is supported by the positive responses from netizens and the interactions that occur in the comments section. Instagram users show interest in visiting the featured attractions after viewing the promotional video content and invite friends and family in the like and comment sections, where they can also ask questions about the place. In addition, Instagram users can interact with each other.